2006
DOI: 10.1136/adc.2006.094029
|View full text |Cite
|
Sign up to set email alerts
|

Community associated MRSA: an alert to paediatricians

Abstract: Community associated methicillin resistant Staphylococcus aureus (CA-MRSA) is an emerging pathogen typically associated with skin and soft tissue infection, with occasional reports of fatality in previously healthy children and young adults. We report a case of invasive CA-MRSA and highlight the potential impact of such infections on empirical treatment of staphylococcal infections.A n 11 year old boy of African origin was admitted to his local hospital with left hip pain, fever, and an inability to weight bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Review of the literature revealed that invasive CA-MRSA infections have (Table 2). This report supports the suggestion that aggressive antistaphylococcal therapy should be initiated in critically ill patients with suspected MRSA infection and shifted to less aggressive therapy as soon as culture results are obtained and MRSA is excluded [16]. CA-MRSA is usually associated with soft tissue superficial infections [14]; however, it may cause invasive and severe infections and even deaths in previously healthy children [5,12].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Review of the literature revealed that invasive CA-MRSA infections have (Table 2). This report supports the suggestion that aggressive antistaphylococcal therapy should be initiated in critically ill patients with suspected MRSA infection and shifted to less aggressive therapy as soon as culture results are obtained and MRSA is excluded [16]. CA-MRSA is usually associated with soft tissue superficial infections [14]; however, it may cause invasive and severe infections and even deaths in previously healthy children [5,12].…”
Section: Discussionsupporting
confidence: 73%
“…Βesides, it seems that PVL is involved in invasive CA-MRSA infections [17]. Questions for the most appropriate empirical therapy are emerging, as initial therapy in critically ill patients appears to be of paramount importance for outcome of patients [16].…”
mentioning
confidence: 99%
“…The largest series was in the seminal paper by Gillet et al [4] who reported 12 deaths. Forty-three survivors have been reported in total [4,17,29,[35][36][37][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], resulting in an overall fatality rate of 62% in these reported cases.…”
Section: Incidence Of Pvl-associated Pneumoniamentioning
confidence: 98%
“…49 The extension and linkage of such systems beyond hospitals to public health information systems may have value as resistant organisms previously confined to inpatient settings migrate to the community. 50,51 …”
Section: Pediatric-specific Featuresmentioning
confidence: 99%